Low dietary diversity and micronutrient adequacy among lactating women in a peri-urban area of Nepal. Issue 17 (31st March 2015) - Henjum, Sigrun; Torheim, Liv Elin; Thorne-Lyman, Andrew L; Chandyo, Ram; Fawzi, Wafaie W; Shrestha, Prakash S; Strand, Tor A
Abstract: Objective: The main objectives were to assess the adequacy of the micronutrient intakes of lactating women in a peri-urban area in Nepal and to describe the relationships between micronutrient intake adequacy, dietary diversity and sociodemographic variables. Design: A cross-sectional survey was performed during 2008–2009. We used 24 h dietary recall to assess dietary intake on three non-consecutive days and calculated the probability of adequacy (PA) of the usual intake of eleven micronutrients and the overall mean probability of adequacy (MPA). A mean dietary diversity score (MDDS) was calculated of eight food groups averaged over 3 d. Multiple linear regression was used to identify the determinants of the MPA. Setting: Bhaktapur municipality, Nepal. Subjects: Lactating women ( n 500), 17–44 years old, randomly selected. Results: The mean usual energy intake was 8464 (sd 1305) kJ/d (2023 (sd 312) kcal/d), while the percentage of energy from protein, fat and carbohydrates was 11 %, 13 % and 76 %, respectively. The mean usual micronutrient intakes were below the estimated average requirements for all micronutrients, with the exception of vitamin C and Zn. The MPA across eleven micronutrients was 0·19 (sd 0·16). The diet was found to be monotonous (MDDS was 3·9 (sd 1·0)) and rice contributed to about 60 % of the energy intake. The multiple regression analyses showed that MPA was positively associated with energy intake, dietary diversity, women's educational level and socio-economic status, and was higher in the winter. Conclusions: The low micronutrient intakes are probably explained by low dietary diversity and a low intake of micronutrient-rich foods.